2013
DOI: 10.1111/eve.12024
|View full text |Cite
|
Sign up to set email alerts
|

Maxillectomy and mandibulectomy in the horse: Indications and necessity of post operative adjunct therapy

Abstract: http://onlinelibrary.wiley.com/doi/10.1111/eve.12002/abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Complete excision by rostral mandibulectomy is the most commonly reported successful treatment in horses with ossifying fibromas . Incomplete removal of ossifying fibromas has been associated with reoccurrence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete excision by rostral mandibulectomy is the most commonly reported successful treatment in horses with ossifying fibromas . Incomplete removal of ossifying fibromas has been associated with reoccurrence .…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile ossifying fibromas are locally invasive tumors often occurring on the rostral part of the mandible . Complete excision of these tumors by rostral mandibulectomy can be curative and results in a good functional and cosmetic outcome . This procedure is simple if a portion of the symphysis can be preserved.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in size and osteolysis suggested malignancy. The rostral localisation of the tumour has been frequently described in horses and surgical therapy, local application of cisplatin and radiation has been specified as treatment attempts (Witte 2014). Intralesional chemotherapy has low success rates in ameloblastic carcinoma (De Cock et al 2003) but there is little information in equine oral neoplasms (Knottenbelt and Kelly 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This neoplasia occurs more often in horses younger than one year of age (ROBBINS et al, 1996;SPONSELLER et al, 2006;CRIJNS et al, 2015), but has been reported in several other species (ROGERS & GOULD, 1998;McCAULEY et al, 2000). Unilateral rostral maxillectomy and bilateral rostral mandibulectomy (BRM) with adequate margins have been considered curative surgical procedures and the best approaches to treat this neoplasia (AUER, 2006;WITTE, 2014). Radiation alone has also been reported to be successful (ROBBINS et al, 1996) and may be helpful as an adjuvant therapy in cases of incomplete surgical resection (WITTE, 2014).…”
mentioning
confidence: 99%
“…Unilateral rostral maxillectomy and bilateral rostral mandibulectomy (BRM) with adequate margins have been considered curative surgical procedures and the best approaches to treat this neoplasia (AUER, 2006;WITTE, 2014). Radiation alone has also been reported to be successful (ROBBINS et al, 1996) and may be helpful as an adjuvant therapy in cases of incomplete surgical resection (WITTE, 2014). Although, successful BRM has already been performed in horses and is described in the literature (AUER, 2006;SPONSELLER et al, 2006; DIXON & REARDON, 2015), these reports fail to mention any complications or the difficulty of the horse to adapt and feed properly after surgery.…”
mentioning
confidence: 99%